Phase Edges, Quantifier Float and the Nature of (Micro-) Variation - Henry, Alison (IBERIA: An International Journal of Theoretical Linguistics, 2014)
This paper considers quantifier float off wh-elements in varieties of West Ulster English. It establishes that there are several sub-dialects of West Ulster English and not just the single variety described by McCloskey (2000); these varieties differ in the positions in which floated quantifiers associated with wh-elements can appear. The full range of possible positions includes not only the highest CP, the first-merge position of the wh-element and the edge of intermediate CPs, as observed by McCloskey, but also the edge of intermediate vPs, providing evidence that wh-movement transits the edge of vP phases. Dialects vary in the range of positions in which a floated quantifier is possible, and in some a floated quantifier cannot occur in the first-merge position of the wh-elements, but only in intermediate positions. Comparing quantifier float off wh-elements with quantifier float off DPs, which is possible in a wider range of language varieties including standard English, the paper offers a possible solution to the puzzle of why quantifier float off DPs is not generally possible in the first-merge position of the DPs in passives and unaccusatives: UG prescribes the positions where elements appear or transit and thus where copies occur, but individual grammars select a subset of those positions as possible for pronunciation of a floated quantifier.